Dunia Imajinasi Ibnu 'Arabi: Kreativitas Imajinasi dan Persoalan DIversitas Agama - CHITTICK, William C (Risalah Gusti, 2001)
Dunia Imajinasi Ibnu 'Arabi: Kreativitas Imajinasi dan Persoalan DIversitas Agama